Labour productivity in agricultural sector of Sub-Sahara Africa (2010–2017): A data envelopment and panel regression approach. Issue 2 (23rd September 2019) - Ibidunni, Ayodotun Stephen; Ufua, Daniel E.; Okorie, Uchechukwu Emena; Kehinde, Busola E.
Abstract : Purpose: The purpose of this paper is to focus on investigating labour productivity in the agricultural sector of Sub-Sahara Africa (SSA) countries between the periods of 2010 and 2017. Design/methodology/approach: The study adopted descriptive design. The sample size for this research includes 43 SSA nations. Measuring SSA nation's agricultural productivity in this study was based on input and output factors relating to the labour resource utilisation between the periods of 2010 and 2017. Data envelopment analysis (DEA) and panel regression analysis were carried out to examine labour productivity within the set periods. Findings: The findings from the study suggest that labour productivity in the agricultural sector of SSA countries can be improved from its presently low state of productivity. The statistical analysis showed that between the periods of 2010 and 2013, only about 34.9 per cent of countries in the region were technically efficient in the utilisation of labour resources for productive use. More disturbing was that, from 2014 to 2017, labour productivity drooped to 11.6 per cent. Meanwhile, employment of labour in the agricultural sector revealed as low as 1.58 percentage to crop production index in the region. Notably, there is the potential of labour employment to derive as high as 80 per cent yield to the gross domestic product of economies in the SSA region. Practical implications: Considering the strategic role of labour to the agricultural sector of SSA countries, there must be a stakeholders approach to stimulating the interest of the populace of these countries and getting them actively involved in the agricultural sector. This imply that government, investors, support agencies from developed economies and populace of the SSA nations must support the drive towards agricultural productivity of the SSA nations. Originality/value: This study established a research agenda that involved a paradigm shift from the more rampant literature on foreign investments, agricultural research, rural livelihood and well-being, among others to focusing on issues that pertain to labour productivity for sustainable agricultural yields in SSA countries. Also, the methodology adopted in the study, such as application of DEA and regression analysis to panel data, shows a departure from single units of analysis adopted by existing studies.